Correlation between Soil Phospor (P) Content and Soil Yeast Antagonistics Ability Against Fusarium oxysporum Pathogen Causing Wilt - Muhibuddin, Anton; Wibowo, Kartika Novitasari; Punnapayak, Hunsa; Goetz, Peter (Universitas KH. A. Wahab Hasbullah, 2017)
Besides its role during fermentation process, yeast also has potential as biological agent because of its antagonistics characteristic. We have isolated yeast from six different locations based on Phospourus differences. Isolated yeast were then tested its antagonistics ability of Fusarium oxysporum, the pathogen causing tomato wilt disease. This research aims to find out the diversity of yeast found in the tomato rhizosphere in six different contents of phosphorus locations and to know its antagonistics ability against the pathogenic. F. oxysporum. This research was conducted in the Laboratory of Mycology, Department of Pests and Diseases, Faculty of Agriculture, Brawijaya University, Malang and in the Chemistry Laboratory, Institut Teknologi 10 Nopember Surabaya, started from January up to September 2015. Yeasts have been isolated from tomato’s rhizosphere of 6 different locations around East Java proviences. The result showed that yeasts from organic field (Lower P content) were 6 genera. They are Candida sp. 1, Pichia sp. 1, Hansenula sp., Metschnikowia sp. 1, Cryptococcus sp., and Zygosaccharomyces sp. While the yeasts from inorganic field (higher P) were 3 genera. The most potential yeast in controlling F. oxysporum is Pichia sp. 2. Lower P content showed more divers than higher P content. Yeasts from higher soil P content showed more antagonists to control F. oxysporum. Keywords: Phosphor, correlation, yeast, antagonistic, disease, soil